PENGARUH KOMUNIKASI, KERJASAMA, KREATIVITAS TERHADAP KINERJA PNS DI BADAN PENDAPATAN DAERAH (BAPENDA) DI KABUPATEN PASER - Ahmad Faisal; Ismail; Faridah Islamiah (PIRSAP (Paser Institute for Scientific Research and Publications), 2023)
The purpose of this study was to determine the effect of communication, teamwork, creativity on the performance of civil servants at the Regional Revenue Agency (BAPENDA) of Paser Regency. From the results of the validity test of the 18 valid statements and the significant limit of rtable 0.05 and the two-tailed test, the rtable value is 0.2876 while rcount > rtable for each statement in this study. The results of the reliability test of the Cronbach Alpha value were 0.903 the value of N of items 18. From the results of data analysis and data tabulation, it can be seen that the results of the regression equation Y = 0.477+0.404X1+0.245X2+0.242X3. Based on the calculation results, the R value (coefficient correlation) of 0.842 is at the relationship level of 0.80-1.000, which means that there is a very strong relationship between the variables Communication (X1), Teamwork (X2), and Creativity (X3) on Employee Performance (Y). Adjusted R Square value (coefficient of determination) is 0.688 or 68%. This shows that the variables Communication (X1), Teamwork (X2), and Creativity (X3)) contribute or contribute an effect of 80.9% on the Performance of Civil Servants (Y) at the Regional Revenue Agency (BAPENDA) Paser Regency . while the remaining 32% is influenced by other variables not included in this study.